A Contrastive Study of Indonesian and American Compliments (A Socio - Pragmatic Approach) - Rusdin, Rusdin (STKIP Al-Amin Dompu, 2016)
The purpose of this study is to identify and classify the types of topic of compliments, the functions and the compliment responses conveyed by the Indonesian and American. The data in this study were taken from each of the two films, namely;